Intraoperative Findings during Canal Wall Down Mastoidectomy in Children - Shrestha, S; Kafle, P (Journal of Nepal Paediatric Society, 2011)
Objective: The main objective of this study is to assess the intraoperative finding during canal wall down mastoidectomy in paediatric patients undergoing surgery for unsafe type of chronic suppurative otitis media (CSOM) attending ENT OPD of Kathmandu Medical College. Materials and Methods: Fifty patients of age group 4 to 13 years who were suffering from unsafe type of CSOM with or without cholesteatoma were taken for the study. The study period was two years from April 2007 to March 2009. The operative findings like extent of cholesteatoma in different location of middle ear cleft, mastoid bony landmarks, and ossicular chain condition and otogenic complication were identified during canal wall down mastoidectomy. Result: Of the 50 patients 32 (64%) were boys and 18(36%) were girls. The age ranged from 4 years to 13 years. Majority of patients had cholesteatoma with granulation diseases (72%) followed by granulation diseases (16%). Involvement of disease in attic, aditus, antrum and mesotympanum were found to be high in majority of cases (82%) with high percentage of necrosis of incus (56%). Conclusion: The primary disease found in patients undergoing canal wall down mastoidectomy (CWDM) was cholesteatoma combined with granulation in72%, granulation in 16% and cholesteatoma in12%. Key words: Canal Wall Down; ENT; Mastoidectomy; Chronic Suppurative Otitis Media (CSOM) DOI: http://dx.doi.org/10.3126/jnps.v31i3.5357 J Nep Paedtr Soc 2011;31(3):184-187